Conflicting rewards: effects of task goals on attention for alcohol cues. Issue 4 (18th May 2020) - Godara, Malvika; Van Bockstaele, Bram; Wiers, Reinout W.
ABSTRACT: Research has shown that temporary task goals capture more attention than negative, threatening cues, even in anxious individuals. In the current study, we investigated whether temporary task goals would also capture more attention than alcohol-related cues. In Experiment 1, 59 hazardous drinkers performed both a modified dot-probe and a flanker task in which temporary goal- and alcohol-relevant stimuli were presented together. Results of the dot-probe task confirmed an attentional bias towards goal-relevant stimuli in the presence of alcohol cues. This effect was absent in a modified flanker task, although there was a general slowing when the targets appeared on top of goal-relevant stimuli, suggesting that goal-related backgrounds captured more attention than alcohol backgrounds. In Experiment 2, we replicated the dot-probe procedure in 29 hazardous drinkers who had been exposed to a prime dose of alcohol prior to performing the task. Our findings indicate that temporary goal stimuli are more salient than alcohol cues, which might lead the way to novel clinical applications.